Prosigna Risk of Recurrence score and intrinsic subtypes are associated with adjuvant anthracycline chemotherapy benefit in high-risk breast cancer - Maj-Britt Jensen; Torsten O. Nielsen; John Bartlett; Anne-Vibeke Lænkholm; Lois Shepherd; Bent Ejlertsen (npj Breast Cancer)
Abstract NCIC-CTG MA.5 and DBCG 89D are symmetrically designed randomized trials comparing adjuvant cyclophosphamide, epirubicin, and fluorouracil with cyclophosphamide, methotrexate, and fluorouracil in high-risk breast cancer patients. In a joint analysis we evaluate the predictive value in terms of anthracycline benefit of molecular subtyping by PAM50. A statistically significant interaction (P = 0.008) between continuous Risk of Recurrence (ROR) score and treatment regimen is evident, translating into a clear distinct treatment effect according to ROR score category with HR 0.51 for ROR score ≥ 72 and HR 1.10 for ROR score < 52 (Pinteraction = 0.004). The analysis provides evidence of the benefit from anthracycline in HER2-enriched subtype; for patients with discordance of HER2 subtype and clinical HER2 status, HER2-enriched subtype was predictive of anthracycline benefit whereas clinical HER2 positive status was not. Anthracycline-based adjuvant chemotherapy may safely be withheld for patients with a low ROR score while the benefit increases with increasing ROR score.